INFLUENCE OF FAT CONTENT ON THE QUALITY AND SHELF LIFE OF CURED SARDINES. - DEVADASAN, K; MURALIDHARAN, V; JOSEPH, GEORGE (Fishery Technology, 2017)
The paper presents results of studies on the effect of seasonal variations in the fat content on the quality and shelf life of dry cured, pickle cured and smoke cured oil sardines. The merits and defects of each method of curing during different seasons are discussed